Drought stress by growth stage and onion plant growth - Richwine, Paul Allen, author; Moore, Frank D., III, advisor; Danielson, Robert E., committee member; Wallner, Stephen J., committee member (Colorado State University. Libraries, 1984)
Three distinct growth stages of the onion's vegetative development have been defined: early (73-101 days), mid (102-122 days), and late season (123-143 days). Two years of field experiments and a greenhouse study with onions examined the effects of drought stress applied during these stages. Influence of excessive nitrate salts was also investigated. Rootview boxes submerged in a furrow-irrigated onion field allowed for a continuous study of root, leaf, and bulb development. A drought stress of -100 kPa soil matric potential was imposed for three weeks during each growth stage. Soil matric potential of -55 kPa was used as a standard. Onion plants located in the greenhouse were hydroponically grown in cans containing half-strength Hoagland's solution. Polyethylene glycol (PEG 3500) was used as the osmotic potential modifier creating drought stresses of -100 kPa and -200 kPa which were applied for 3 weeks during each growth stage. Ammonium nitrate (NH4NO3) at levels of 153 and 202 ppm NO3-N provided the high nitrate source. Both field and greenhouse studies identified the mid-season growth stage as the most sensitive to drought stress equal to or greater than -100 kPa. Bulb, root, and top components were significantly reduced as compared with the no stress treatment. Drought stress of -100 kPa during the early season growth stage had no significant negative effect on onion growth, however, a drought stress of -200 kPa applied during the early season growth stage caused growth to be suppressed. Drought stress had no significant effect on onion growth when applied during the late season growth stage. There was no significant influence of high nitrate levels on onion top, bulb, or root growth.
Covers not scanned.
Keywords: Onions -- Irrigation; Growth (Plants); Plants -- Water requirements